Russia and Islam - Yemelianova, G. author. aut Link
XXIV, 244 p.
Keywords: The end of communism has revived the historical debate about Russia's relations with both the West and the East. Some commentators viewed the Russian-Chechen war as a clash of civilizations, which would shape the future relationships between the new Russia and its Muslim periphery and perhaps lead to its disintegration. But the reality has challenged this scenario. This book surveys the public and private relations between Russia and Islam and concludes these are more complex than is usually recognized.